Normative values for optical coherence tomography parameters in healthy children and interexaminer agreement for choroidal thickness measurements - Turan,Kadriye Erkan (2018)
ABSTRACT Purpose: To (a) determine the normative values for optical coherence tomography (OCT) parameters such as central macular thickness, retinal nerve fiber layer thickness, and choroidal thickness in healthy children; (b) investigate the relationships of these parameters with axial length, central corneal thickness, refractive errors, and intraocular pressure; and (c) determine interexaminer agreement for choroidal thickness measurements. Methods: In this cross-sectional study, 120 healthy children aged 8-15 years underwent detailed ophthalmological examination and OCT measurements. Choroidal thickness was measured at three separate locations by two independent examiners. Results: The mean global retinal nerve fiber layer thickness was 98.75 ± 9.45 μm (79.0-121.0). The mean central macular thickness was 232.29 ± 29.37 μm (190.0-376.0). The mean subfoveal choroidal thickness obtained by examiner 1 was 344.38 ± 68.83 μm and that obtained by examiner 2 was 344.04 ± 68.92 μm. Interexaminer agreement was between 99.6%-99.8% for choroidal thickness at three separate locations. Central macular thickness increased with axial length (r=0.245, p=0.007). Choroidal thickness increased with age (r=0.291, p=0.001) and decreased with axial length (r=-0.191, p=0.037). Global retinal nerve fiber layer thickness decreased with axial length (r=-0.247, p=0.007) and increased with central corneal thickness (r=0.208, p=0.022). Global retinal nerve fiber layer thickness positively correlated with choroidal thickness (r=0.354, p<0.001). Global retinal nerve fiber layer thickness (r=0.223, p=0.014) and choroidal thickness (r=0.272, p=0.003) increased with the spherical equivalent (D). Conclusions: Optical coherence tomography parameters showed a wide range of variability in children. Retinal nerve fiber layer thickness, central macular thickness, and choroidal thickness were found to be either inter-related or correlated with age, central corneal thickness, axial length, and refractive errors. Furthermore, manual measurements of choroidal thickness showed high interexaminer agreement. Because normative values for optical coherence tomography parameters differed in children, the measurements should be interpreted according to an age-appropriate database.